Blackouts mitigation of power system using fuzzy technique - Siti Nur Ain, Abdul Kadir (2012)
Recently, power system protection devices have often been blamed for contributing to system disturbance. Indeed, current major blackouts found that false tripping of these devices play an important role in initiating and propagating cascading events. Various reasons have been declared for these failures. In this project, the main objective is to develop a technique based on fuzzy to reduce blackouts during emergency conditions. The first stage of this project is power flow analysis which is used to find the input data to apply to fuzzy technic. In the second stage, fuzzy logic method is used to detect the capability of power that should be shedding from the system in case of line outage happen in the power system. The proposed fuzzy technic is tested on IEEE 5 and 30-bus system utilizing the MATLAB. The presented results versify show that by using the proposed technique various power system blackouts may be prevented.